Menstrual disturbance associated with COVID-19 vaccines: A comprehensive systematic review and meta-analysis - Kunchok Dorjee; R. C. Sadoff; Farima Rahimi Mansour; Sangyal Dorjee; Eli M. Binder; Maria Stetson; Regina Yuen; Hyunju Kim (PLoS ONE, 2025)
Background The relationship between COVID-19 vaccines and menstrual disturbance is unclear, in part because researchers have measured different outcomes (e.g., delays vs. changes to cycle length) with various study designs. Menstrual disruption could be a decisive factor in people’s willingness to accept the COVID-19 vaccine. Methods We searched Medline, Embase, and Web of Science for studies investigating menstrual cycle length, flow volume, post-menopausal bleeding, and unexpected or intermenstrual bleeding. Data were analyzed using fixed-effects meta-analysis with Shore’s adjusted confidence intervals for heterogeneity. Findings Seventeen studies with >1·9 million participants were analyzed. We found a 19% greater risk of increase in menstrual cycle length as compared to unvaccinated people or pre-vaccination time-periods (summary relative risk (sRR): 1·19; 95% CI: 1·11–1·26; n = 23,718 participants). The increase in risk was the same for Pfizer-BioNTech (sRR: 1·15; 1·05–1·27; n = 16,595) and Moderna vaccines (sRR: 1·15; 1·05–1·25; n = 7,523), similar for AstraZeneca (sRR: 1·27; 1·02–1·59; n = 532), and higher for the Janssen (sRR: 1·69; 1·14–2·52; n = 751) vaccine. In the first cycle after vaccination, length increased by <half-day (summary mean difference (sMD): 0·34 days; 0·21–0·46 days; n = 30,320) after the first dose and by 0·62 days (sMD: 0·62: 0·41–0·82; n = 17,608) after the second dose. In the second cycle after vaccination, the risk was not elevated (sMD: –0·02; –0·16–0·12; n = 18,602). The increase in risk was between 7–9% but statistically insignificant for heavier flow; 7% for post-menopausal bleeding (first dose: 1·07; 1·01–1·12; n = 1,321,268 and second dose: 1·07; 1·03–1·11; n = 1,482,884); and 16–41% for unexpected or intermenstrual bleeding (first dose: 1·16; 0·83–1·61; n = 1,303,687 and second dose: 1·41; 0·99–2·01; n = 1,390,317). Interpretation We observed a mild increase in the risk of menstrual disturbance associated with COVID-19 vaccines. Such risks are likely clinically unmeaningful. Vaccine recipients should be appropriately counseled.